THE UTILIZATION OF INSTAGRAM AS A SOCIAL MEDIA IN ENHANCING THE CADETS’ ABILITY TO WRITE A RECOUNT TEXT - Sulistyorini, Dwi; Haryani, Haryani (Majalah Ilmiah Gema Maritim, 2022)
Abstract The objective of this research was about finding out if there is a significantly different use of the Instagram media for increasing the cadets’ ability to write Recount text in Technical Department compared to the use of English book media on students' ability to write short recount texts. The samples in this study were two classes of cadets of the Technical Department, Politeknik Bumi Akpelni involving 48 cadets. The experimental group was taught using Instagram as a new way of learning through social media in sample groups and groups taught using English books or handouts in non-examples groups. To find out whether there is an important difference between the final examination scores of the sample and non-sample groups, the t-test was calculated, and it was found that the t-value was higher than the t-table (3, 109 > 2.00). According to the results of the research that has been carried out for 1 semester, the researchers conclude that there is an important effect on using the new method, namely the Instagram social media application, compared to the use of English books or handouts that have been used the old way on the cadets' ability to write recount texts. This means that the t-test is greater than the t-table. The alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. In addition, through a new method of following young people's technology, namely social media Instagram as a medium in teaching English, especially recount text, it is very significant to improve cadets' writing skills.